Новые факты из истории заселения Слободской Украины (по этнографическим материалам Харьковской области) - Маслюченко, С. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
New facts about the history of settlement Sloboda Ukraine (ethnographic materials of the Kharkiv region)